Beyond Whole-Body Imaging: Advanced Imaging Techniques of PET/MRI. (February 2015) - Barnwell, James; Raptis, Constantine A.; McConathy, Jonathan E.; Laforest, Richard; Siegel, Barry A.; Woodard, Pamela K.; Fowler, Kathryn
Abstract : Abstract: PET/MRI is a hybrid imaging modality that is gaining clinical interest with the first Food and Drug Administration–approved simultaneous imaging system recently added to the clinical armamentarium. Several advanced PET/MRI applications, such as high-resolution anatomic imaging, diffusion-weighted imaging, motion correction, and cardiac imaging, show great potential for clinical use. The purpose of this article is to highlight several advanced PET/MRI applications through case examples and review of the current literature.